Pay-for-performance as a cost-effective implementation strategy: results from a cluster randomized trial - Garner, Bryan R. (Implement Sci, 2018)
BACKGROUND: Pay-for-performance (P4P) has been recommended as a promising strategy to improve implementation of high-quality care. This study examined the incremental cost-effectiveness of a P4P strategy found to be highly effective in improving the implementation and effectiveness of the Adolescent Community Reinforcement Approach (A-CRA), an evidence-based treatment (EBT) for adolescent substance use disorders (SUDs). METHODS: Building on a $30 million national initiative to implement A-CRA in SUD treatment settings, urn randomization was used to assign 29 organizations and their 105 therapists and 1173 patients to one of two conditions (implementation-as-usual (IAU) control condition or IAU+P4P experimental condition). It was not possible to blind organizations, therapists, or all research staff to condition assignment. All treatment organizations and their therapists received a multifaceted implementation strategy. In addition to those IAU strategies, therapists in the IAU+P4P condition received US $50 for each month that they demonstrated competence in treatment delivery (A-CRA competence) and US $200 for each patient who received a specified number of treatment procedures and sessions found to be associated with significantly improved patient outcomes (target A-CRA). Incremental cost-effectiveness ratios (ICERs), which represent the difference between the two conditions in average cost per treatment organization divided by the corresponding average difference in effectiveness per organization, and quality-adjusted life years (QALYs) were the primary outcomes. RESULTS: At trial completion, 15 organizations were randomized to the IAU condition and 14 organizations were randomized to the IAU+P4P condition. Data from all 29 organizations were analyzed. Cluster-level analyses suggested the P4P strategy led to significantly higher average total costs compared to the IAU control condition, yet this average increase of 5% resulted in a 116% increase in the average number of months therapists demonstrated competence in treatment delivery (ICER = $333), a 325% increase in the average number of patients who received the targeted dosage of treatment (ICER = $453), and a 325% increase in the number of days of abstinence per patient in treatment (ICER = $8.134). Further supporting P4P as a cost-effective implementation strategy, the cost per QALY was only $8681 (95% confidence interval $1191–$16,171). CONCLUSION: This study provides experimental evidence supporting P4P as a cost-effective implementation strategy. TRIAL REGISTRATION: NCT01016704.